Evacuation from tunnels - an example of the Straževica tunnel - Jevtić, Radoje B. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Tunnels are passageways built for different purposes: road tunnels, railway tunnels, subway tunnels or similar. Their dimensions are becoming more and more considerable, depending on technology improvement. According to the fact that many people and vehicles pass continually through these structures, there was a logical question about a possible evacuation in case of disasters such as fire, explosion or similar. This is a constantly open and actual problem, confirmed by many people who perished in disasters because they could not be evacuated or because an evacuation was delayed for some reasons. This paper has been written to show a possible evacuation situation and to calculate the minimum time for the evacuation in the case of 772 m long Straževica tunnel.